A closer look at the work behavior of Gen Z in Micro, Small, and Medium Enterprises of developing countries - I. Astuty; R. Astuti; S. Mahmud; V. Widodo (International Journal of Human Capital in Urban Management)
BACKGROUND AND OBJECTIVES: The management of human resources focusing on workplace happiness is gaining significant attention in the study of organizational behavior, particularly in organizations hiring Gen Z. This generation perceives workplace happiness differently, making the factor crucial in understanding work behavior. Therefore, this study aimed to explore the role of workplace happiness as a mediator between motivation and performance among employees in Micro, Small, and Medium Enterprises in developing countries.METHODS: The study adopted a survey design, obtaining data from 186 young workers across 23 MSMEs in developing countries. Path analysis was also used to test the proposed model.FINDINGS: The first results in this study showed that motivation significantly affected happiness at work with a p-value of 0.000 below the specified significance level of ≤0.005 (5%). The second result also showed that motivation significantly influenced performance with a similar p-value of 0.000. The third result suggested that happiness at work exhibited a significant effect on performance with a p-value threshold. Finally, the study found that happiness at work mediated the relationship between motivation and performance as evidenced by a p-value of 0.000.CONCLUSION: The study suggested that motivation positively affected happiness at work and further enhanced performance. Additionally, job satisfaction could serve as a mediator between motivation and performance. Cultivating a work environment that prioritizes teamwork, and mutual respect, as well as discourages self-serving behavior could further improve employee happiness, job satisfaction, and overall performance. This improvement would also benefit MSMEs by enhancing work quality and productivity.